The Impact of Gauge Cluster Displays on Driver Attention and Mental Workload: An Eye-Tracking Study - Oh, Seeung; Kim, Sungju; Im, Youngjae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
With the increasing digitalization of automotive interfaces, optimizing gauge cluster design is crucial for minimizing driver cognitive load and distraction. Gauge clusters contain critical driving-related information linked directly to safety, such as speed, fuel levels, and warning indicators, which drivers must quickly and accurately perceive. This study uses eye tracking to examine the impact of analog and digital gauge clusters on driver attention. Thirty participants viewed driving videos to search for information while their eye movements were recorded. The first experiment compared analog and digital clusters, revealing that digital displays allowed faster visual searches and reduced cognitive effort. The second experiment analyzed digital clusters with various dash types and colors. The results indicate that the dual-dash digital display with a white background was the most effective in the cluster design. This research provides practical guidelines for the cluster design to increase driving engagement and decrease the cognitive workload on drivers. Therefore, the results will encourage automotive interface designers to consider ergonomic directions for gauge clusters from a user-centered perspective.